Active control of free and forced vibration of rotating laminated composite cylindrical shells embedded with magnetostrictive layers based on classical shell theory - Shahin Mohammadrezazadeh; Ali Asghar Jafari (Mechanics of Advanced Composite Structures)
In this study, active control of free and forced vibration of rotating thin laminated composite cylindrical shells embedded with two magnetostrictive layers is investigated by means of classical shell theory. The shell is subjected to harmonic load which is exerted to inner surface of the shell in thickness direction.  The velocity feedback control method is used in order to obtain the control law. The vibration equations of the rotating cylindrical shell are extracted by means of Hamilton principle while the effects of initial hoop tension, centrifugal and Coriolis accelerations are considered in the vibration equations. The differential equations of the rotating cylindrical shell are converted to ordinary differential equations by means of modified Galerkin method.  The displacement of the shell is obtained using modal analysis. The free vibration results of this study are validated by comparison with the results of open literature. Also, the validity of the forced vibration results is proved by comparison with the fourth order Runge-Kutta method's result. Finally, the effects of several parameters including circumferential wave number, rotational velocity, the whole orthotropic layers thickness, magnetostrictive layers thickness, length, the amplitude and exciting frequency of the load on the vibration characteristics of the rotating cylindrical shell are investigated.